Next-Generation Sensors with Three-Dimensional Micro-/Nano-Structures - Kim, Jang Hwan; Lee, Su Eon; Park, Jun Hyun; Jin, Ho Jun; Choe, Jun Seok; Ko, Janghun; Kim, Bong Hoon (Journal of Sensor Science and Technology, 2024)
Innovative sensor technologies are crucial in various fields, including environmental monitoring, healthcare, and industrial appli-cations. Sensor fabrication at the nano/microscale and the introduction of 3D structures can improve the sensitivity, response time, and overall performance of the sensor. Specifically, 3D architectures allow improved surface areas and interactions with target substances, whereas miniaturization facilitates improved sensitivity and integration into compact devices. This review discusses the recent advance-ments in five types of sensors, namely, gas sensors, strain sensors, environmental sensors, photodetectors, and biosensors, emphasizing the importance of structural innovations and size reduction in enhancing sensing capabilities. The essential design, fabrication methods, and potential applications are explored, highlighting the transformative impact of these technologies on future sensor development.
Keywords: Flexible sensor; Micro/nano sensor; Soft electronic sensor; Stretchable sensor; Three-dimensional (3D) sensor